Rejuvenating Aged Hematopoietic Stem Cells Through Improvement of Mitochondrial Function - Moon, James; Kim, Hye Ran; Shin, Myung Geun (Annals of laboratory medicine, 2018)
Mitochondria are the powerhouses of the cell as well as the primary site of hematopoiesis, which also occurs in the cytoplasm. Hematopoietic stem cells (HSCs) are characterized by a very high turnover rate, and are thus considered to be relatively free from the age-related insults generated by mitochondria. However, HSCs are also subject to these age-related insults, including the incidence of myeloid proliferative diseases, marrow failure, hematopoietic neoplasms, and deterioration of the adaptive human immune system. Recently, NAD⁺ dietary supplements, known as niacin or vitamin B₃, including tryptophan, nicotinic acid, nicotinamide, and the newly identified NAD⁺ precursor nicotinamide riboside, have been shown to play a role in restoring adult stem cell function through the amelioration of mitochondrial dysfunction. This insight motivated a study that focused on reversing aging-related cellular dysfunction in adult mouse muscle stem cells by supplementing their diet with nicotinamide riboside. The remedial effect of nicotinamide riboside enhanced mitochondrial function in these muscle stem cells in a SIRT1-dependent manner, affecting cellular respiration, membrane potential, and production of ATP. Accordingly, numerous studies have demonstrated that sirtuins, under nuclear/mitochondrial control, have age-specific effects in determining HSC phenotypes. Based on the evidence accumulated thus far, we propose a clinical intervention for the restoration of aged HSC function by improving mitochondrial function through NAD⁺ precursor supplementation.